CURATORIAL PAINTINGS BY I WAYAN BENDI AND IDA BAGUS INDRA COLLECTION OF THE RUDANA MUSEUM - Ginting, Serevina Rikel Carroland; Kondra, I Wayan; Gulendra, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
The internship at the Rudana Museum provided valuable experiences in the curatorial field, deepening the author's understanding of the curator's role in preserving and showcasing art collections. The author participated in exhibition projects, including background research on artworks and collection preparation. The works of artists like I Wayan Bendi and Ida Bagus Indra were analyzed to understand the philosophical, spiritual, and social meanings they embody. During the internship, the author evaluated the need for in-depth research, team coordination, and communication strategies for different audiences. The author also analyzed the stylistic differences between I Wayan Bendi's more experimental and contemporary works and Ida Bagus Indra's classical and detailed pieces. These differences reflect the variations in their experiences and approaches to Balinese fine art in the modern context. This internship provided insights into the challenges and opportunities in curatorial work, highlighting the importance of teamwork and dedication to cultural heritage preservation. The experience enriched the author's practical knowledge and expanded their understanding of the importance of collection accessibility through educational approaches and public programs.